EFFECTS OF OLMESARTAN ON LOCAL AND REGIONAL RIGIDITY OF ARTERIES IN ISCHEMIC HEART DISEASE - I. B. Matrosova; E. A. Melnikova; V. E. Oleynikov (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To evaluate 24-week treatment by olmesartan on rigidity of arteries in different vessel areas in patients with coronary heart disease (CHD) with 1–2 grade arterial hypertension (AH).Material and methods. Into open-label, non-randomized trial 25 patients with CHD and 1–2 grade AH were included. During 24-week treatment period patients received olmesartan medoxomil 20–40 mg daily. Baseline and final parameters of arterial wall stiffness were measured using ultrasound method with echotracking. The thickness of intima-media (TIMC) was defined. To evaluate regional vessel stiffness the volume sphygmography method was used.Results. Acorrding to the data of volume sphygmography terapy by olmesartan significantly decrease PWVao by 19,4%, R-PWV b L-PWV — by 11,9% and 11,6% (p<0,05). CAVI1 decreased by 9,3%; L–CAVI1 — by 13,7%, CAVI2 — на 14,9% (p<0,05). В-PWV did not change significantly. During 24-week medication treatment the regress of carotid atherosclerosis was marked: decrease of TIMC from 773,6±155,7 μm to 736,3±124,1 μm (p<0,05). The values loc P sys and loc P dia significantly decreased by 13,5% and 11% (p<0,05); rigidity index β by 19,1% (p<0,05). Also we marked the increase of transverse pliability by 3,3% (p<0,05) and decrease of loc PWV by 17% (p<0,05). The coefficient of transverse pliability, locAix and DOCA did not show significant changes.Conclusion. Addition of olmesartan to the standard treatment of CHD and AH showed significant improvement of local and regional stiffness.